2018
DOI: 10.1016/j.jpeds.2018.01.034
|View full text |Cite
|
Sign up to set email alerts
|

The Population Impact of Childhood Health Conditions on Dropout from Upper-Secondary Education

Abstract: More than one fifth of educational dropout is attributable to childhood health conditions. Early-onset mental disorders emerge as key targets in reducing dropout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 66 publications
1
23
1
1
Order By: Relevance
“…However, and as expected, the HC had a higher educational level compared with people with mental disorders. Indeed, people with mental disorders, particularly with psychotic features, often do not complete the educational path, especially when they have an early onset, in childhood or adolescence (Frissen et al, ; Mikkonen, Moustgaard, Remes, & Martikainen, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, and as expected, the HC had a higher educational level compared with people with mental disorders. Indeed, people with mental disorders, particularly with psychotic features, often do not complete the educational path, especially when they have an early onset, in childhood or adolescence (Frissen et al, ; Mikkonen, Moustgaard, Remes, & Martikainen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among longitudinal studies, plausibly less affected by reverse causation, and other causal inference studies, only some support a detrimental impact of overweight/obesity in childhood on educational outcomes [19][20][21][22] . There is also mixed evidence for asthma [23][24][25][26][27] and rarer health conditions [23][24][25]28,29 . The impact on school absence, and any mediating role of school absence in explaining associations of health with educational attainment, also likely differs by condition [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…The impact on school absence, and any mediating role of school absence in explaining associations of health with educational attainment, also likely differs by condition [30][31][32] . A link with school absence is clearer for migraine 26,33 and depression 34 , than for asthma 23,27,31 , ADHD 24,35 , ASD 24,36 or obesity [37][38][39][40] .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been documented that the vocational schools have the highest dropout rates in upper secondary education in Finland (Official Statistics of Finland 2015). Research has also supported the premise that substance abuse, mental health problems, and drop-out of education often co-occur among these students (Luopa et al 2014;Mikkonen et al 2018). Indeed, it has been found that differences in health-related behaviors are elucidated by family background factors (i.e., family structure, parents' education, and occupation status) and the close interplay between different forms of substance abuse (i.e., alcohol, tobacco, and drugs) (Ruokolainen and Mäki 2015).…”
mentioning
confidence: 96%